Fluxo: A System for Internet Service Programming by Non-expert Developers - Kiciman, Emre; Livshits, Ben; Musuvathi, Madan; Webb, Kevin C. (ACM Symposium on Cloud Computing, 2010)
Over the last 10–15 years, our industry has developed and deployed many large-scale Internet services, from e-commerce to social networking sites, all facing common challenges in latency, reliability, and scalability. Over time, a relatively small number of architectural patterns have emerged to address these challenges, such as tiering, caching, partitioning, and pre- or post-processing compute-intensive tasks. Unfortunately, following these patterns requires developers to have a deep understanding of the trade-offs involved in these patterns as well as an end-to-end understanding of their own system and its expected workloads. The result is that non-expert developers have a hard time applying these patterns in their code, leading to low-performing, highly suboptimal applications. In this paper, we propose FLUXO, a system that separates an Internet service’s logical functionality from the architectural decisions made to support performance, scalability, and reliability. FLUXO achieves this separation through the use of a restricted programming language designed 1) to limit a developer’s ability to write programs that are incompatible with widely used Internet service architectural patterns; and 2) to simplify the analysis needed to identify how architectural patterns should be applied to programs. Because architectural patterns are often highly dependent on application performance, workloads and data distributions, our platform captures such data as a runtime profile of the application and makes it available for use when determining how to apply architectural patterns. This separation makes service development accessible to non-experts by allowing them to focus on application features and leaving complicated architectural optimizations to experts writing application-agnostic, profile-guided optimization tools. To evaluate FLUXO, we show how a variety of architectural patterns can be expressed as transformations applied to FLUXO programs. Even simple heuristics for automatically applying these optimizations can show reductions in latency ranging from 20-90% without requiring special effort from the application developer. We also demonstrate how a simple shared-nothing tiering and replication pattern is able to scale our test suite, a web-based IM, email, and addressbook application.